Standing upright against trauma and hardship: Checklists of innovative moments of social and psychological resistance - Muhammed Furkan Cinisli (International Journal of Narrative Therapy and Community Work, 2024)
Trauma represents a profound and emotionally intense experience within the human condition. Beyond its evident impacts on both the physiological and psychological dimensions of an individual, this complex phenomenon encapsulates moments of resistance and strength in the face of adversity. From a narrative standpoint, individuals invariably manifest unique responses to trauma, which necessitate a close and nuanced examination for recognition and comprehension. This article proposes a framework for the systematic collection and organisation of diverse responses to trauma through a checklist of innovative moments of social and psychological resistance, contributing to a greater comprehension of this intricate phenomenon.